2016
DOI: 10.1038/srep23989
|View full text |Cite
|
Sign up to set email alerts
|

Revealing a new activity of the human Dicer DUF283 domain in vitro

Abstract: The ribonuclease Dicer is a multidomain enzyme that plays a fundamental role in the biogenesis of small regulatory RNAs (srRNAs), which control gene expression by targeting complementary transcripts and inducing their cleavage or repressing their translation. Recent studies of Dicer’s domains have permitted to propose their roles in srRNA biogenesis. For all of Dicer’s domains except one, called DUF283 (domain of unknown function), their involvement in RNA substrate recognition, binding or cleavage has been po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 55 publications
0
38
0
4
Order By: Relevance
“…Very recently, we showed that the DUF283 domain of hDicer can bind 12-nt ssRNA in vitro, though the observed binding was very weak (Kurzynska-Kokorniak et al, 2016). Here, we demonstrated that the full length hDicer does not bind such short ssRNAs (Fig.…”
Section: Binding Between Hdicer and Single-stranded Rnas Of Differentmentioning
confidence: 50%
See 1 more Smart Citation
“…Very recently, we showed that the DUF283 domain of hDicer can bind 12-nt ssRNA in vitro, though the observed binding was very weak (Kurzynska-Kokorniak et al, 2016). Here, we demonstrated that the full length hDicer does not bind such short ssRNAs (Fig.…”
Section: Binding Between Hdicer and Single-stranded Rnas Of Differentmentioning
confidence: 50%
“…Finally, DUF283 has been found to be responsible for interactions with Dicer protein partners (Ota et al, 2013). Moreover, it has been demonstrated that the separate DUF283 domain of Dicer selectively binds single-stranded RNAs (ssRNAs) in vitro, and accelerates annealing of complementary nucleic acids (Kurzynska-Kokorniak et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The DExD/H domain is located in the base of the L and forms a clamp near the RNase III domain active site [1,10]. A recent study showed that the DUF283 domain of Dicer is capable of binding single-stranded nucleic acid [11].
Figure 1.Dicer structure and functions.( A ) The structure of Dicer.
…”
Section: Dicer Structure and Domainsmentioning
confidence: 99%
“…Some paired 19-mers with a dTdT overhang at the 3' end bind Dicer with high affinity; these sequences are not cleaved by Dicer, are fully transferred to Ago and trigger high-efficiency gene silencing activity [10,11]. Dicer also binds single RNAs at a specific site with high affinity, the function of which is to accelerate hybridization with a partner from the "soup" of RNA metabolism [14]. The newly in situ-formed dsRNA, which is asymmetric, slides into the endonuclease site for cleavage, and the processed RNAi product is transferred successfully into RISC complex.…”
Section: Introductionmentioning
confidence: 99%